2007
DOI: 10.1002/cem.1041
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temperature variations on spectroscopic calibration modelling: a comparative study

Abstract: Abstract:Temperature fluctuations can have a significant impact on the repeatability of spectral measurements and as a consequence can adversely affect the resulting calibration model. More specifically, when test samples measured at temperatures unseen in the training data set are presented to the model, degraded predictive performance can materialize. Current methods for addressing the temperature variations in a calibration model can be categorized into two classescalibration model based approaches, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The water has absorption peaks at 840 nm, 970 nm, 1190 nm, 1450 nm, and 1940 nm due to a combination of different overtones of OH stretching and bending bands. This temperature shift complicates calibration models based on NIR for samples with varying temperature, since this effect has to be accounted for (Chen & Martin, 2007). On the other hand, the phenomenon can also be used to monitor the temperature in materials.…”
Section: Introductionmentioning
confidence: 99%
“…The water has absorption peaks at 840 nm, 970 nm, 1190 nm, 1450 nm, and 1940 nm due to a combination of different overtones of OH stretching and bending bands. This temperature shift complicates calibration models based on NIR for samples with varying temperature, since this effect has to be accounted for (Chen & Martin, 2007). On the other hand, the phenomenon can also be used to monitor the temperature in materials.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Peirs et al [11] who concluded that representative calibration sets to cover the temperature range expected in the future seemed to be the best option for measurement of the soluble solids contents of apples under unstable temperature conditions. Also Chen and Martin [17] undertook a comparison of the predictive performance of a number of temperature correction techniques and concluded that the global modeling approach achieved the best predictive performance.…”
Section: Resultsmentioning
confidence: 98%
“…Difficulty with temperature variations in the open path occur in both industrial and atmospheric measurements. Degraded predictive performance of calibration models in which the temperatures of calibration and prediction differ is a known problem [39,40]. Quantitative interpretation of spectra at varying temperatures is difficult [41].…”
Section: Algorithm For the Determination Of Gas Concentrations Based mentioning
confidence: 99%